Increasing Customer Loyalty Through E-Service Quality and Satisfaction: A Study on Muamalat Islamic Digital Applications - Umar, St Hafsah; T, Andi Marhuni (Amsir Accounting & Finance Journal, 2024)
Technological advances have made it easier for various business activities, including production, marketing, sales, and transactions. Technology has given birth to terms such as E-business and E-commerce, changing the way transactions are carried out without the need for a physical presence or cash payment. Now, cashless transactions can be made quickly and efficiently through mobile devices connected to the internet. This study aims to examine the influence of E-Service Quality on Customer Loyalty with Customer Satisfaction as an Intervening Variable. Using a quantitative approach with 186 samples of M-DIN users at Bank Muamalat KCP GOWA, data analysis was carried out through descriptive statistical analysis and path analysis. The results show that E-Service Quality has a positive and significant effect on Customer Loyalty, and Customer Satisfaction can mediate this influence on MDIN users.